2019
DOI: 10.1007/s00167-019-05423-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related morphological differences in sulcus angle and condylar height for the femoral trochlea using magnetic resonance imaging

Abstract: PurposeThis study aimed to elucidate the primary differences in trochlear morphology between men and women utilizing three‐dimensional magnetic resonance image reconstruction of the femoral trochlea. MethodsDifferences in anthropometric femoral trochlea data of 975 patients (825 women, 150 men) were evaluated. The following morphological parameters were measured at three flexion angles (15°, 30°, and 45°) of the femoral trochlea: the sulcus angle, condylar height, and the trochlear groove orientation and medio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
(74 reference statements)
1
29
0
Order By: Relevance
“…6). Recently, a three-dimensional morphology study showed a gender difference for femoral posterior condylar offset and condylar height for the femoral trochlea in the Korean population (Koh et al, 2019b;Koh et al, 2019c). This study provides guidelines for the design of a suitable femoral component for TKA considering gender-specific differences in the Korean population (Koh, Nam, Chung, Kim, Chun and Kang, 2019b;Koh, Nam, Chung, Lee, Kim, Kim and Kang, 2019c).…”
Section: Fig 5 Schematic Of a Subject-specific Musculoskeletal Modelmentioning
confidence: 75%
“…6). Recently, a three-dimensional morphology study showed a gender difference for femoral posterior condylar offset and condylar height for the femoral trochlea in the Korean population (Koh et al, 2019b;Koh et al, 2019c). This study provides guidelines for the design of a suitable femoral component for TKA considering gender-specific differences in the Korean population (Koh, Nam, Chung, Kim, Chun and Kang, 2019b;Koh, Nam, Chung, Lee, Kim, Kim and Kang, 2019c).…”
Section: Fig 5 Schematic Of a Subject-specific Musculoskeletal Modelmentioning
confidence: 75%
“…The TEA projection technique was applied on the tibia as described by Akagi et al 7 and Bonnin et al 22 . The use of 3-D reconstructions in radiology for descriptive anatomical studies or examination of pathologic lesions is well guided in previous studies 7, [22][23][24] . Using these techniques, the number of available subjects is larger, and their demographic data are accessible.…”
Section: Discussionmentioning
confidence: 99%
“…First, MRI scans were used to develop the 3D representations of the femur and tibia in this study, and there could be some errors in the computation model. Nevertheless, the reconstruction soft tissues such as the articular cartilage needs to be performed on MRI, and potential inaccuracies in 3D reconstructions could be reduced using protocols used in our previous studies 23 , 24 . Second, our population lacks ethnic diversity, and the results might differ in other populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulcus angle and Insall-Salvati ratio were confirmed to be within normal limits for all knees. 12,24 None of the specimens showed signs of advanced degeneration during inspection using knee arthroscopy. Specimens consisted of 25 cm of the femur and tibia.…”
Section: Specimen Preparationmentioning
confidence: 96%